2020
DOI: 10.3389/fpls.2020.00089
|View full text |Cite
|
Sign up to set email alerts
|

The Integration of Spring and Winter Wheat Genetics With Agronomy for Ultra-Early Planting Into Cold Soils

Abstract: Early seeding has been suggested as a method of increasing the grain yield and grain yield stability of wheat (Triticum aestivum L.) in the Northern Great Plains. The point at which early seeding results in a decrease in grain yield has not been clearly identified. Changes in climatic conditions have increased frost-free periods and increased temperatures during grain filling, which can either be taken advantage of or avoided by seeding earlier. Field trials were conducted in western Canada from 2015 to 2018 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(37 citation statements)
references
References 23 publications
1
35
1
Order By: Relevance
“…Durum wheat yield losses in Australia are primarily due to water stress (Liu et al, 2015) similar to well-published studies in wheat from lack of rainfall during spring which causes a mild water deficit stress prior to anthesis, moderate stress at anthesis and becomes more severe during grain fill (French and Schultz, 1984). Agronomic solutions to maintain yield and reduce potential exposure to water stress, heat and frost can be achieved by manipulating plant development and sowing date (Bassu et al, 2009;Collier et al, 2020). To facilitate the timing of optimal flowering, growers need to match a genotype development speed with sowing date.…”
Section: Seeding Systems -Seed Treatments For Abiotic Stress Resistancementioning
confidence: 62%
See 2 more Smart Citations
“…Durum wheat yield losses in Australia are primarily due to water stress (Liu et al, 2015) similar to well-published studies in wheat from lack of rainfall during spring which causes a mild water deficit stress prior to anthesis, moderate stress at anthesis and becomes more severe during grain fill (French and Schultz, 1984). Agronomic solutions to maintain yield and reduce potential exposure to water stress, heat and frost can be achieved by manipulating plant development and sowing date (Bassu et al, 2009;Collier et al, 2020). To facilitate the timing of optimal flowering, growers need to match a genotype development speed with sowing date.…”
Section: Seeding Systems -Seed Treatments For Abiotic Stress Resistancementioning
confidence: 62%
“…The authors report that grain yield was not compromised and often maximized when seeding occurred at around 2 o C soil temperature. A greater reduction in grain yield was observed when planting was delayed until soil reach 10 o C, despite extreme environmental conditions after initial seeding, including air temperatures as low as −10.2 o C and as many as 37 nights with air temperatures below 0 o C (Collier et al, 2020). An opportunity associated with such a system that results in earlier maturity is a refined integrated pest management strategy.…”
Section: Seeding Systems -Seed Treatments For Abiotic Stress Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…A short frost-free period is commonly referenced as a grain yield-limiting factor on the northern Great Plains; however, increases in the average frost-free period from 1961 to 2018 are rarely referenced as contributing to wheat grain yield increase [4][5][6][7]. Ultra-early wheat seeding systems based on soil temperature triggers as described in Collier et al [8] can produce greater grain yield by capturing the benefits of longer frost-free periods: early season growing degree-day accumulation, increased vegetative growth periods, early season precipitation, increased day-length at anthesis and reduced average temperatures at grain fill.…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating wheat and small grain cereals seeding dates reported the greatest yield resulted from the earliest seeding dates [15][16][17][18][19]. However, these studies initiated plantings based on an arbitrary calendar date, meaning the planting times within individual seasons were not standardized to account for variability between growing seasons, an issue accounted for by moving to soil temperature-triggered seeding in the study conducted by Collier et al [8]. Multiple studies have identified earlier seeding as an important method to avoid grain yield reduction caused by increased growing season temperatures [8,14,20,21].…”
Section: Introductionmentioning
confidence: 99%